Efficacy of Topical Azithromycin versus Systemic Doxycycline in Treatment of Meibomian Gland Dysfunction - Marwa Aly Zaky; Adel Galal Zaky; Moataz Fayez Elsawy; Kareem Fatehy Shehata; Mohamed Samy Abd Elaziz (Journal of Ophthalmology)
Background. Ocular surface disease (OSD) is a multifactorial and highly frequent problem. Inadequate or unstable tear film is the main cause, which leads to visual impairments. One of the primary causes of OSD is meibomian gland dysfunction (MGD), with a prevalence of 3.5 to 70%. The aim of this work was to compare the efficacy of azithromycin topical eye drops versus oral doxycycline in MGD individuals. Methods. This prospective comparative cohort research was carried out on 56 patients of both sexes of any age with symptomatic MGD. Randomly, patients were classified into two equal groups: Group 1 was treated twice daily for 4 weeks with topical azithromycin 1% eye drops, while group 2 received oral doxycycline 100 mg capsules twice daily for 4 weeks. Results. In the 1st follow-up, there was a significant difference between the studied groups in pain and discomfort degree (P value = 0.024) as group 1 showed a higher number of patients with a mild pain degree (P value = 0.013) while group 2 showed a higher number of patients with a severe pain degree (P value = 0.022). There was an insignificant difference between the studied groups in moderate pain degree and lid margin telangiectasia. Conjunctivitis, frothy discharge, and meniscus floaters were significantly higher in group 2 than in group 1 (P value = 0.013, 0.028, and 0.031, respectively). In group 1, the break-up time test was significantly higher than in group 2 (P value = 0.023). In the 2nd follow up, in group 2 only meniscus floaters were significantly higher than in group 1 (P value = 0.044), while in group 1 break-up time test was significantly higher than in group 2 (P value = 0.029). Otherwise, there is no significant difference between both the groups. Conclusions. Meibomian gland dysfunction (MGD) could be treated effectively with oral doxycycline and topical azithromycin by improving symptoms, clinical signs, and stabilization of tear film. Moreover, the topical azithromycin group seemed to be superior over the oral doxycycline group in improving the quality of tear film in the short term, having fewer side effects, more compliance, and better tolerability.